Effects of Different Gastric Residual Volume Thresholds on Morbidity and Mortality in Patients Receiving Intensive Care - Esra Çankaya; Sertaç Çankaya; Ahmet Oğuzhan Küçük; Hülya Ulusoy (Galenos Yayinevi, 2021)
Objective:Enteral feeding is often limited by gastrointestinal intolerance. However, there is no consensus on the threshold value of gastric residual volume (GRV) on adjusting the enteral feeding rate. This study aimed to determine the effects of GRV thresholds of 150 mL and 250 mL on reaching calorie and protein targets and to determine gastric intolerance in patients receiving intensive care and enteral feeding.Materials and Methods:In this retrospective study, patients who were treated and followed in the intensive care unit (ICU) of our clinic between 2008 and 2017 were examined for 14 days after hospitalisation. Caloric values, protein values, presence of gastric intolerance, morbidity, and mortality factors of the patients, who were divided into two groups with 150 mL (group 1) and 250 mL (group 2) GRV thresholds, were examined.Results:The amounts of calories and proteins provided after 14 days were significantly higher in group 2 (p<0.001), and the cumulative calorie and protein deficits were significantly less in group 2 (p<0.001). As regards morbidity and mortality, no significant difference was observed in aspiration pneumonia, anaemia, disseminated intravascular coagulation, septic shock, reintubation, intensive care mortality, 28th day mortality, and number of mechanical ventilation-free days between the two groups. The incidence of nosocomial infection (p=0.002) and ventilator-associated pneumonia (p<0.001) was significantly higher and the duration of mechanical ventilation (p<0.001) and length of stay in the ICU (p<0.001) was significantly longer in group 2 than in group 1. No statistically significant difference was observed between the two groups in terms of the development of gastrointestinal intolerance during follow-up (p=0.896).Conclusion:Target nutritional values were reached in both groups. No pathological side effects of excessive intervention were observed in the group with lower tolerance. Similarly, no valuable morbidity or mortality result was obtained for the 250 mL threshold.